The Role of Emotional Intelligence and Self-Efficacy in Predicting Academic Achievement of Medical Students - Aisya Alya Iqlima Rizfahdilla; Rihadini Pudjo; Gharini Sumbaga Narhadina (CV. Publikasi Indonesia, 2026)
Academic achievement among medical students is often measured using the Grade Point Average (GPA), which reflects a student's overall academic performance throughout the course of study. Medical students face substantial academic demands that frequently result in moderate to severe levels of stress. Emotional intelligence, encompassing self-motivation, emotional regulation, empathy, and teamwork, has been shown to influence academic performance, while students with high self-efficacy tend to achieve better academic outcomes. This study aimed to examine the relationships between emotional intelligence, self-efficacy, and GPA, both individually and simultaneously. An analytical observational study with a cross-sectional design was conducted. The participants consisted of 108 medical students from Universitas Muhammadiyah Semarang, selected through purposive sampling. Emotional intelligence was measured using the Trait Emotional Intelligence Questionnaire–Short Form (TEIQue-SF), and self-efficacy was assessed using the Academic Self-Efficacy Scale (TASES). Bivariate analysis was performed using the Mann–Whitney U test, while multivariate analysis was conducted using multinomial logistic regression. The majority of respondents demonstrated high emotional intelligence but low self-efficacy, and most had a high GPA. There was no significant association between emotional intelligence and GPA or between self-efficacy and GPA, and neither variable showed a significant independent effect in the multivariate analysis. However, emotional intelligence and self-efficacy jointly had a significant effect on GPA. In conclusion, emotional intelligence and self-efficacy were not individually associated with GPA; however, together they significantly influenced GPA, although other factors likely also contributed to the academic performance of these medical students.